Long-term cardiac MRI follow up of MANTICORE (Multidisciplinary Approach to Novel Therapies in Cardio-Oncology REsearch) - Dina Labib; Mark Haykowsky; Emer Sonnex; John R. Mackey; Richard B. Thompson; D. Ian Paterson; Edith Pituskin (Cardio-Oncology)
Abstract Background This study investigates the long-term cardiac effects of trastuzumab-based chemotherapy in early breast cancer (EBC) survivors. We extend the original MANTICORE trial which showed that angiotensin-converting enzyme inhibitors (ACEI) and beta-blockers (BB) could mitigate the decline in left ventricular (LV) ejection fraction (EF) during the first year of trastuzumab treatment. Objectives We hypothesized that, over time, cardiac function would decline further and adverse changes in cardiac geometry would occur due to the aging of the population and prior treatment. Methods The study enrolled 52 participants from the original MANTICORE trial cohort, with cardiac magnetic resonance (CMR) imaging conducted at a median of 6.5 years post randomization to treatment. Results We found that, contrary to the hypothesis, participants maintained LV EF over the follow-up period. Specifically, the placebo group exhibited a recovery in LV EF to levels comparable with the treatment groups, suggesting no long-term differential impact on cardiac function. However, a significant reduction in LV mass was observed across all groups, the clinical implications of which remain unclear. Conclusions The findings suggest that in a selected population receiving trastuzumab-based chemotherapy, extended cardiac imaging surveillance beyond one-year post-treatment may be unnecessary. We posit that the presence of HER2 overexpressing breast cancer influenced hypertrophic changes to cardiac geometry observed at baseline and one year, which resolved after completing HER2-blocking treatment. The study also highlights the need for further research to understand the significance of changes in cardiac geometry during and after breast cancer treatment​.